Survival of Listeria monocytogenes during storage of soft cheeses Galotyri and Touloumotyri at 5°C and 12°C - PAPAGEORGIOU (Δ. Κ. ΠΑΠΑΓΕΩΡΠΟΥ) D. K.; BORI (Μ. ΜΠΟΡΗ) M.; MANTIS (Α. ΜΑΝΤΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Soft spreadable cheeses Galotyri and Touloumotyri were inoculated with Listeria monocytogenes strains Scott A or California (CA), to contain 3.6-7.5 x 105 CFU/g of cheese and stored at 5°C and 12°C f or 30d and 40d respectively. The initial pH of the cheeses Galotyri and Touloumotyri were 4.35 (S.D.±0.08) and 4.53 (S.D. ±0.06) respectively, and remained relatively constant during the entire experiment. Fat in dry mater was 50.06% (S.D. ±1.16) in Calotyri and 37.43% (S.D. ±0.62) in Touloumotyri cheese. Values of moisture content of cheeses were 68.04% (S.D. ±0.36) and 73.01% (S.D.±0.14) respectively. The NaCl content for Galotyri and Touloumotyri cheeses was 1.54% (S.D.±0.12) and 1.03% (S.D. ±0.10) respectively. Duplicate samples of cheeses were used for enumeration of L. monocytogenes and pH. Listeria counts were obtained by surface plating on lithium chloride phenylethanol moxalactam agar (LPM). Selected Listeria colonies were confirmed biochemically. Viability loss of L. monocytogenes in Galotyri cheese was rapid, but the pathogen survived for more than 40 d in Touloumotyri cheese. During storage of Galotyri cheese at 5°C and 12°C, population of both strains of L. monocytogenes decreased significantly (P<0.01) to less than 10 viable cells/g of cheese, within 7 to 16 d for 7 trials. At that time population of L. monocytogenes decreased by 2.9-4.55 Log10 CFU/g. Estimated D-value was 2.17 d (S.D. ±1.02) for the 7 trials. Only for one trial L. monocytogenes was counted up to 24 d, but was not survived more than 26 d. The reduction of population was statistically significant (P<0.01) for this trial also. Cold enrichment up to 8 weeks of samples in which L. monocytogenes was not counted, indicated that the pathogen survived for 16 d up to 27 d in a l l trials. Both strains of L. monocytogenes survived for more than 40 d during storage of Touloumotyri cheese at 5°C and 12°C. Population of L. monocytogenes decreased significantly (P<0.05) by 0.98 to 1.96 Log10 CFU/g during storage of Touloumotyri cheese at 5 °C and 12 °C. After 40d of storage of cheese, populations of the pathogen ranged from 5.3 to 51 χΙΟ3 CFU/g. Calculation indicated that survivors of the pathogen represent the 1.1% up to 10.6% of the initial population of L. monocytogenes inoculated to the cheese.